COMPARISON OF CELL CYCLE DURATION IN THE MONOLAYER CELL LINE OF HEPATOMA ZAJDELA AND ITS SUBLINES 3H AND 9C CULTIVATED IN VITRO - Petrov, Yu P; Teryukova, N P; Sahenberg, E I; Ivanov, V A; Snopov, S A (T͡S︡itologii͡a, 2017)
We studied proliferative features of cells in monolayer line of rat hepatoma Zajdela (the original, parent line) and in the sublines 3H and 9C cloned from different types of the colonies of the parental line. These sublines also differed by cytomorphometric parameters, by the types of colonies formed at recloning of these cells in vitro, and by tumorogenicity at transplantation to a rat. Using a time-lapse video of native living cells, we analyzed the cell cycle duration (CCD) and its relationship to a cell shape. Direct measurement of the CCD (a time period from mitosis to mitosis) was performed in individual cells of non-synchronized cultures. Average value of CCD in the parent Zajdela line appeared to be 14.6 ± 0.2 hours, that was higher (at P < 0.05) than in 3H and 9C sublines (13.9 ± 0.2 and 13.5 ± 0.3 hours, respectively). The analysis of CCD distribution histogram showed that all three lines contained a common population of cells with CCD close to 14 hours. Besides, the parent cell line had about 1/3 of cells with a higher CCD (16.7 ± 0.2 hours) while the subline 9C had, on the contrary, 1/3 of cells with a lower CCD (12.6 ± 0.1 hours). In addition, the parameters of cell area, coefficient of cell spreading and coefficient of cell polarization showed the highest correlation to CCD in cells of subline 3H, which are primarily fibroblast-shaped cells (P < 0.01) : the larger the cell area, the longer the CCD; the more flattened or polarized the cell is, the shorter its CCD. In the parental cell line and the subline 9C, both consisting of preferably epithelium-shaped cells, the correlation between CCD and cell shape was less pronounced and showed the opposite direction, that may be explained by a difference in the origin of the cell lines. When considering the differences of CCD in the pairs of daughter cells, we introduce the concept of «the coefficient of symmetry of a cell division». The lower its value, the greater the similarity of CCD in a pair of daughter cells. Possible connection of the cell parameters studied in vitro to the tumorigenicity of these cells is discussed.